(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
In this paper,we establish the boundedness of parameterized area integral \(μ_Ω,S^ρ\) and the Littlewood-Paley \(g_λ^*\) function \(μ_Ω,λ^*,ρ\) with variable kernel on weighted Morrey space \(L^p,k(ω)\).